Effect of storage time and chlorhexidine addition on the mechanical properties of glass ionomer cements - Machado, Juliana de Carvalho [UNESP]; de Oliveira, Josânia Pitzer; Duque, Cristiane [UNESP]; Scarparo, Angela (Universidade Estadual de Campinas, 2018)
Aims: To evaluate the effect of the chlorhexidine (CHX) incorporation and the storage time on the mechanical properties of glass ionomer cements (GICs). Methods: The following GICs were evaluated: Ketac Molar Easymix (KM), Vidrion R (VR) and Vitromolar (VM), containing or not CHX. GIC liquid was modified by adding 1.25 % CHX digluconate and then manipulated with the power and placed into the stainless steel cylindrical or bar-shaped molds. GICs specimens were stored into water for 1, 7 and 28 days. After these periods, specimens were submitted to flexural, diametral tensile and compressive strength tests, according to ISO standards. Data from mechanical tests were statistically analyzed using 2-way ANOVA and Tukey tests. Results: Overall, the storage time did not influence any of the mechanical properties of the GICs tested. In contrast, the inclusion of CHX reduced significantly these properties for all GICs tested. KM presented the highest values of compressive strength for all storage times. KM + 1.25% CHX had lower compressive strength results than KM, however, it showed similar results when compared to another GICs without CHX. Conclusions: The presence of chlorhexidine, independent of the storage time, interfered on the mechanical characteristics of GIC.
Keywords: Chlorhexidine; Dental caries; Glass ionomer cements; Mechanical properties; Water storage